The complete mitochondrial genomes of Pangasius nasutus and P. conchophilus (Siluriformes: Pangasiidae) - Abdul Halim, Siti Amalia Aisyah; Esa, Yuzine; Gan, Han Ming; Zainudin, Amir Asyraf; Mohd Nor, Siti Azizah (Taylor and Francis, 2023)
The catfish, Pangasius nasutus and P. conchophilus, are often misidentified between each other due totheir similar morphology. Thus, the current study was conducted to differentiate them based on amolecular approach. The complete mitochondrial genomes of P. nasutus and P. conchophilus obtainedfrom the Pahang River (Peninsular Malaysia) were sequenced, assembled, and annotated using next-generation sequencing (NGS). A 16,465 bp and 16,470 bp length mitogenome sequence of P. nasutusand P. conchophilus, respectively, was generated, each containing 13 protein genes, 22 tRNAs, and tworRNAs, typical of most vertebrates. This is the first report of the complete mitochondrial genomesequences of P. nasutus and P. conchophilus. These data are a valuable genetic resource for future stud-ies of these two commercially important species.